Behavior of inflation in Colombia 2002-2010 and inflation targeting regime (2013)
Among the objectives of economic policy that have been under study, in all countries and all economies, one is of particular importance with respect to inflation, given its importance on economic activity. This article analyzes the significance of reducing inflation for economies, the characteristics of an inflation targeting regime, the history in Colombia since the independence of the Central Bank, the inflation outcomes in the country 2002-2010, and lastly includes conclusions.